The Reasons for and Basic Principles in Formulating the Hong Kong Special Administrative Region Basic Law, and its Essential Contents and Mode of Expression - Youyu, Zhang (Columbia Journal of Asian Law, 1988)
Hong Kong has always been Chinese territory. However, since late in the Qing Dynasty, it has been ruled by Great Britain. Recently, after peaceful negotiations, the Chinese and British govern- ments signed the Joint Declaration on the Hong Kong Question (Joint Declaration). This agreement stipulates that on July 1, 1997, Great Britain will restore Hong Kong to China, and China will simul- taneously resume the exercise of its full sovereignty over the region. After control of Hong Kong is returned to China, Hong Kong will become an internal administrative region. It goes without saying that all else being equal, Hong Kong would be treated in the same way as all other parts of China. That is, generally applicable national laws would apply to Hong Kong. Thus, what need is there for a Hong Kong Special Administrative Region (SAR) Basic Law? The Basic Law is needed because Hong Kong’s historical background and socio-economic circumstances differ from those of other parts of China. Thus, we must enact exceptional laws appropriate for this exceptional area.